G-banding homologies of a tandem fusion in Paralakhemundi (Swamp) and Crossbred (Murrah x Swamp) buffalo chromosome - Mallick, PK; Ghosh, AK (Journal of Livestock Biodiversity, 2025)
Present cytogenetic study was conducted on Paralakhemundi and crossbred (MurrahXSwamp) buffaloes in Gajapati district of Orissa state. The whole blood culture technique was followed for morphological study of chromosome and for identification and characterization of individual chromosome conventional Giemsa stain solution (pH 6.8) and G-banding procedures were employed in this study. The diploid chromosome number obtained in G-banding procedure in Paralakhemundi and crossbreed buffaloes were 48 (24 pairs) and 49 (24 pairs+1), respectively, in both the sexes and both of them possessed 10 sub-metacentric chromosomes. The chromosomes of crossbred buffalo possessed a longer sub-metacentric autosome at 4th pair in both the sexes in comparison to Paralakhemundi. It is due to homologous translocation and the numerical polymorphism to a balanced tandem fusion between both members of chromosomes 4 and 9 of the Murrah karyotype. A break in the vicinity of the centromere of acrocentric chromosome 9 resulted in fusion of this chromosome to the short arm of the sub-metacentric chromosome 4, which probably broke in its telomeric regions. In morphological study comparison of mean relative percentage length of chromosome between Paralakhemundi and crossbred buffalo in the conventional Giemsa stained, G-banded metaphase chromosome showed that the Giemsa stained chromosomes were smaller than the G-banded chromosomes (not considering the sex chromosome). The mean relative percentage length varied from 1.187±0.002 to 7.231±0.004 in Giemsa stained and 1.211±0.002 to 9.817±0.004 in G-banded Paralakhemundi chromosome however; in crossbred buffaloes it varied from 1.107±0.002 to 11.714±0.005 in Giemsa stained and 1.295±0.003 to 12.510±0.004 in G-banded chromosome. The higher length in the upper side in crossbred (i.e. 11.714 and 12.51) was due to translocation. The centomeric index (%) and the arm ratio of first ten pairs of sub-metacentric chromosomes varied from 37.61 to 47.82 and 1.090 to 1.398 in Paralakhemundi and 34.93 to 48.28 and 1.081 to 1.498 in crossbred buffalo, respectively. The present findings on G-Banding profile could be important in physical gene mapping studies, which can be consider as one of the most important steps for molecular genetics improvement of the domestic animal.